Early Operative Versus Delayed Operative Versus Nonoperative Treatment of Pediatric and Adolescent Anterior Cruciate Ligament Injuries: A Systematic Review and Meta-analysis. Issue 14 (December 2021) - James, Evan W.; Dawkins, Brody J.; Schachne, Jonathan M.; Ganley, Theodore J.; Kocher, Mininder S.; Anderson, Christian N.; Busch, Michael T.; Chambers, Henry G.; Christino, Melissa A.; Cordasco, Frank A.; Edmonds, Eric W.; et al.
Background: Treatment options for pediatric and adolescent anterior cruciate ligament (ACL) injuries include early operative, delayed operative, and nonoperative management. Currently, there is a lack of consensus regarding the optimal treatment for these injuries. Purpose/Hypothesis: The purpose was to determine the optimal treatment strategy for ACL injuries in pediatric and adolescent patients. We hypothesized that (1) early ACL reconstruction results in fewer meniscal tears than delayed reconstruction but yields no difference in knee stability and (2) when compared with nonoperative management, any operative management results in fewer meniscal tears and cartilage injuries, greater knee stability, and higher return-to-sport rates. Study Design: Systematic review and meta-analysis; Level of evidence, 4. Methods: A systematic search of databases was performed including PubMed, Embase, and Cochrane Library using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Inclusion criteria were a pediatric and adolescent patient population (≤19 years old at surgery), the reporting of clinical outcomes after treatment of primary ACL injury, and original scientific research article. Exclusion criteria were revision ACL reconstruction, tibial spine avulsion fracture, case report or small case series (<5 patients), non–English language manuscripts, multiligamentous injuries, and nonclinical studies. Results: A total of 30 studies containing 50 cohorts and representing 1176 patients met our criteria. With respect to nonoperative treatment, knee instability was observed in 20% to 100%, and return to preinjury level of sports ranged from 6% to 50% at final follow-up. Regarding operative treatment, meta-analysis results favored early ACL reconstruction over delayed reconstruction (>12 weeks) for the presence of any meniscal tear (odds ratio, 0.23; P = .006) and irreparable meniscal tear (odds ratio, 0.31; P = .001). Comparison of any side-to-side differences in KT-1000 arthrometer testing did not favor early or delayed ACL reconstruction in either continuous mean differences ( P = .413) or proportion with difference ≥3 mm ( P = .181). Return to preinjury level of competition rates for early and delayed ACL reconstruction ranged from 57% to 100%. Conclusion: Delaying ACL reconstruction in pediatric or adolescent patients for >12 weeks significantly increased the risk of meniscal injuries and irreparable meniscal tears; however, early and delayed operative treatment achieved satisfactory knee stability. Nonoperative management resulted in high rates of residual knee instability, increased risk of meniscal tears, and comparatively low rates of return to sports.